ANALISIS AGROINDUSTRI LEMPUK DURIAN DI DESA SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Dora Felicita Dongoran; Sisca Vaulina (DINAMIKA PERTANIAN, 2019)
Agroindustry is an activity of processing agricultural products to be semi-product or product that has economic value. The purpose of this study was to determine the characteristics of entrepreneurs and agroindustry business profiles of lempuk durian, the use of raw materials, supporting materials, labor, processing technology, and production processes of lempuk durian, the poduction costs, income, efficiency and added value of lempuk durian, and marketing of durian products. The study used survey methods located in Selatbaru Village, Bantan District, Bengkalis Regency, Riau Province. A total of 4 craffsmen was selected as respondents by the census. The data were analyzed by qualitative descriptive and quantitative descriptive approaches. The results showed that the lempuk durian craffsman averaged 47 years old, 12 years old education, 14 years of business experience, and 5 person of family member. Agroindustry profile of lempuk durian was a small-scale industry category. The use of raw materials consisted of durian meat and supporting materials such as sugar, firewood, plastic packing, bunch, string, label, isolation, solar, and gas cylinders. The average use of fixed costs was IDR 1,968,633 per production process, production costs was IDR 15,886,133 per production process, gross income was IDR 26,937,500 per production process and net income was IDR 11,051,367 per production process and RCR value was 1.70 with value-added IDR 51,016. The marketing of lempuk durian had two marketing channels.